Dr. Arthur Buehler obituary. (8th August 2019) - Hermansen, Marcia
Abstract : Comparative Islamic Studies mourns the loss of editorial board member, Dr. Arthur Buehler, who passed away in Tucson, Arizona April 1, 2019. Before pursuing his doctorate at Harvard University under Annemarie Schimmel, he had mastered the Arabic language and spent several years in Yemen and Oman teaching English. Before his retirement Dr. Buehler had been Senior Lecturer in Religious Studies at Victoria University of Wellington, New Zealand. He had also taught Islamic Studies at several American Universities. Art Buehler was a scholar of Sufism, especially the Persianate Sufism of South and Central Asia. In addition to numerous articles, his books include: Sufi Heirs of the Prophet: The Indian Naqshbandiyya and the Rise of the Mediating Sufi Shaykh (1998); Revealed Grace: The Juristic Sufism of Ahmad Sirhindi, 1564–1624 (2011), and Recognizing Sufism: Contemplation in the Islamic Tradition (2016).